2008
DOI: 10.1179/174329408x282587
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of fracture toughness and interfacial shear strength of hard and brittle Cr coating on ductile steel substrate

Abstract: The fracture toughness and interfacial adhesion properties of a coating on its substrate are considered to be crucial intrinsic parameters determining performance and reliability of coatingsubstrate system. In this work, the fracture toughness and interfacial shear strength of a hard and brittle Cr coating on a normal medium carbon steel substrate were investigated by means of a tensile test. The normal medium carbon steel substrate electroplated with a hard and brittle Cr coating was quasi-statically stretche… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
9
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(18 citation statements)
references
References 34 publications
1
9
0
Order By: Relevance
“…9 then deflect into interface cracking or delamination with the increase of tensile stress [30,31] . Therefore, the characteristic frequency spectrums and corresponding dominant bands of an AE signal can be obtained after a series of the FFT analysis.…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
“…9 then deflect into interface cracking or delamination with the increase of tensile stress [30,31] . Therefore, the characteristic frequency spectrums and corresponding dominant bands of an AE signal can be obtained after a series of the FFT analysis.…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
“…Agrawal and Raj (A-R) [ 29 , 30 ] developed an experimental technique and analysis to evaluate the ultimate shear strength of a ceramic-metal interface. Due to its simplicity in experimental setup and its acceptable reliability in property prediction, the A-R model has been widely used in many reported works [ 31 , 32 , 33 , 34 , 35 , 36 , 37 ]. Furthermore, Chen et al [ 21 ] reported their modification of the sinusoidal profile of interfacial shear stress in the original A-R model and test results on a TiN (coating)—304 steel (substrate) system.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, Chen et al [ 21 ] reported their modification of the sinusoidal profile of interfacial shear stress in the original A-R model and test results on a TiN (coating)—304 steel (substrate) system. It is noteworthy to point out that, besides films below or around 1 µm thick [ 19 , 21 , 33 , 36 , 37 , 38 ], coatings of tens or even hundreds of micron thick have also been reported to be tested using the original A-R model [ 31 , 32 , 39 ]. In these experimental papers, defects and residual stress are primarily mentioned and discussed as factors that are leading to the error in interfacial property prediction, nevertheless, thickness and in-plane stress distribution have been largely overlooked as a potential source of error.…”
Section: Introductionmentioning
confidence: 99%
“…the number of cracks per unit axial distance became a constant after this critical strain [12][13][14][15][16]. Although the number of the cracks remained constant after the critical strain, the crack length or (and) width would increase with the increase of the tensile strain in order to accommodate the applied strain [12][13][14][15][16]. So, a more suitable parameter to characterize the crack density should be presented.…”
mentioning
confidence: 99%
“…The crack density is often defined as the number of the cracks per unit distance [12][13][14][15][16]. It was found that the cracking of the coating initiated at critical strain, and then the number of the cracks of the coating per unit axial distance increased with the increase of the tensile strain [12][13][14][15][16]. At another critical strain, the crack density (the number of the cracks) of the coating became saturated, i.e.…”
mentioning
confidence: 99%